Training Materials for Elementary Schools Social Sciences Teacher Forum - Afni, Nur; Wahid, Abdul; Hamzah, Rahma Ashari (Mimbar Ilmu, 2024)
Subject teacher forum activities, especially in social sciences subjects at the elementary school level, have not shown significant changes in improving teacher abilities. Based on this, this research aims to develop materials for elementary schools social sciences teacher forum. This type of research is development research (Research and Development or R&D) by adapting two research and development models, namely the Borg and Gall model and the Dick and Carey model. The research subjects involved 3 experts who assessed the training materials: material experts, design experts, and language experts. The research respondents were social sciences teacher forum administrators or managers, instructors or resource persons, and 20 teachers. The techniques used in collecting data were observation, questionnaires, interviews, and documentation. The instrument used to collect data was a questionnaire sheet. The techniques used for data analysis are qualitative and quantitative descriptive analysis. The research results, namely the results of validity tests by learning material experts, obtained an average value of 3.58 (valid). The assessment by the training materials design expert was 3.75 (valid). The assessment from language experts is 3.57 (valid). The effectiveness test results obtained an average value from the calculation results, namely 4.27 (very effective). It was concluded that the social sciences teacher forum training materials were declared suitable for use. It indicates that the training materials are very effective for use in the social sciences teacher forum. The implication of this research is that the MGMP IPS training materials developed can be used to improve teacher abilities.